Pancasila sebagai Sistem Etika : Analisis Nilai-Nilai Fundamental dan Implementasinya di Indonesia - Ahmad Muhamad Mustain Nasoha; Ashfiya Nur Atqiyah; Rahdatu Cahya Puranita; Inas Lutfiyah; Salsyabila Apriliyani (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
Pancasila, as the foundation of the Indonesian state, plays an important role as an ethical system that guides national and state life. This study aims to explore and analyze how the values of Pancasila as an ethical system. The research method used is a literature study. Through this approach, various sources of literature such as textbooks, journal articles, academic papers, and legal documents are collected and critically analyzed. The results of this study indicate that the five principles of Pancasila, namely Belief in the One Almighty God, Just and Civilized Humanity, Unity of Indonesia, Democracy Guided by the Wisdom of Deliberation/Representation, and Social Justice for All Indonesian People each contain fundamental values. This study identifies the need for a more integrative approach in translating the principles of Pancasila into real policies and actions.